The Driver, Pressure, State, Impact, Response (DPSIR) approach in analyzing the case of waste emergencies in Bandung City - Rochman, Syaiful; Ramdani, Jaka; Tampubolon, Lydia Irianti (Journal of Agrosociology and Sustainability, 2024)
Background: As the center of development and education in West Java, the city of Bandung has faced a waste problem that continues to increase along with increasing population growth. Indeed, there were two tragedies. In 2005 the Leuwigajah landfill exploded and in 2023 the Sarimukti landfill was burned. These tragedies became the climax of the Waste Emergency in the city of Bandung. Methods: By using the Driver, Pressure, State, Impact, Response (DPSIR) framework and the literature research, this study aimed to gain a better understanding of the urban waste problem faced by each region, especially the city of Bandung. Findings: It was found that the government's Response only addresses Pressure and State, while Driving Force and Impact have not yet been addressed. Conclusion: From these results, it is recommended to raise awareness among residents of the city of Bandung through real appeals and persuasions, and to require manufacturers to be responsible for the distribution of their products. Novelty/Originality of this Study: The application of the DPSIR framework to analyze and address waste management emergencies in Bandung, Indonesia. While this method has been applied in various contexts, it has not been specifically tailored to the unique challenges of this region. This approach underscores the importance of addressing both immediate waste management issues and underlying consumer behaviors. It provides a comprehensive strategy that involves the engagement of the government, private sector, and community.